Rekonstruksi Teks Dari Buku “Nanti Juga Terbiasa” Karya Helo Bagas - Harahap, Dewi An-nisa; Harahap, Rosmawati (Jurnal Penelitian Multidisiplin Ilmu, 2024)
This research aims to reconstruct the text from the book "Nanti Also Get Used" by Helo Bagas. The focus of this research is to analyze the intrinsic and extrinsic elements in the text and make it into a novel. The approach used is a qualitative approach with descriptive methods. The data source for this research is the text from the book "Later You Get Used to It". The data collection techniques used were library research and note-taking techniques. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the research show that the reconstruction of the text "Later Also Gets Used to" reveals themes about the dynamics of life and social changes that occur in society. Reconstruction of the text "Later You Get Used to" provides a deeper understanding of the meaning contained in the book, especially in relation to the dynamics of life and social changes that occur in society.